(untitled) (Colloquia Comparativa Litterarum, 2025)
This article is an introduction to the thematic section of the journal Colloquia Comparativa Litterarum (volume 11, 2025). The paper is dedicated to the theme “Dialogues, Continuity, Openness: Comparative Perspectives in the 21st century”. A definition of the three concepts is proposed in the light of the key stages in the evolution of French comparative literature throughout the 20th and into the 21st century. The transition from classical comparatism to post-classical comparatism presupposes the diversification of methods and a certain decompartmentalisation of disciplines. Each of the articles presented in this introduction follows (at least) one comparative line in accordance with the new paths taken by the discipline: dialogues between literature and the arts or sciences, dialogues between continents (Europe and Africa), between periods (the Middle Ages and the contemporary period), parallels between similar women’s writings, but also between feminist solidarities and writings, and finally, the continuity of classical comparative studies, which are evolving towards a post-classical broadening of the subjects, objects, and methods.